THE INFLUENCE OF INFORMATION TECHNOLOGY ON CHRONIC PATIENT HEALTH MANAGEMENT - Awan Setiawan; Toto Suharto; Tuhfatul Ulya (CV. Adiba Aisha Amira, 2024)
The digital age has revolutionized the management of chronic patient health with advanced information technology (IT) integration. The study aims to evaluate the impact of information technology on the efficiency, quality, and accessibility of health care for chronic patients. The research method is literary study. Research results show that the use of EHRs makes it easier to access and update patient health data in real time, improving the quality of health care. Telemedicine offers facilities for remote consultation, reducing the need for frequent physical visits, thereby increasing the efficiency of care. Finally, mobile health apps and wearables provide personal and continuous health monitoring, which supports more accurate and informed clinical decision-making. The research concludes that information technology plays an important role in improving health management for chronic patients through improved accessibility, efficiency, and personalization of care.